2013
DOI: 10.1080/10810730.2013.778370
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health in China: A Review of Research and Programs in Medical Care, Health Education, and Public Health

Abstract: There are nearly 1 billion mobile phone subscribers in China. Health care providers, telecommunications companies, technology firms, and Chinese governmental organizations use existing mobile technology and social networks to improve patient-provider communication, promote health education and awareness, add efficiency to administrative practices, and enhance public health campaigns. This review of mobile health in China summarizes existing clinical research and public health text messaging campaigns while hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…Although a couple of previous studies (Corpman, 2013;Li et al, 2014) discussed some societal and environmental conditions of mHealth penetration in the context of China, the current study supplemented the previous literature by uncovering the possible societal consequences of mobile fitness apps from the perspectives of Chinese consumers.…”
Section: Improved Quality Of Life Versus Overdependencementioning
confidence: 98%
See 1 more Smart Citation
“…Although a couple of previous studies (Corpman, 2013;Li et al, 2014) discussed some societal and environmental conditions of mHealth penetration in the context of China, the current study supplemented the previous literature by uncovering the possible societal consequences of mobile fitness apps from the perspectives of Chinese consumers.…”
Section: Improved Quality Of Life Versus Overdependencementioning
confidence: 98%
“…This includes studies of health education, medication adherence, and appointment reminders (Corpman, 2013), the use of mobile technologies to extend health services to rural areas (Ni, Wu, Samples, & Shaw, 2014), and the use of mHealth for mental illness (Zhang, Song, & Bai, 2013). However, much of this research is yet to catch up with the rapid proliferation of smartphones across Asia.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…[10] Studies have confirmed that mobile technology interventions significantly improved an array of health care outcomes such as self-management behavior in Chinese populations. [16] WeChat is one of the most popular social media platforms worldwide, with more than 0.54 billion users in China and worldwide. It offers a free instant messaging application for Smartphones that enable the exchange of voice, text, pictures, videos, and location information via mobile phone indexes.…”
Section: Pushing Electronic Chinese Infographic and Text Information mentioning
confidence: 99%
“…In 2011, the number of mobile phone subscribers in the People’s Republic of China was more than 940 million. During the same period, more than 575 billion text messages were sent 7. The Ministry of Health of the People’s Republic of China is encouraging a greater role of mobile technology in assisting with health education in rural and community public health clinics 7.…”
Section: Introductionmentioning
confidence: 99%
“…During the same period, more than 575 billion text messages were sent 7. The Ministry of Health of the People’s Republic of China is encouraging a greater role of mobile technology in assisting with health education in rural and community public health clinics 7. However, there are few studies that focus on the pre-conditions of mobile phone ownership, text messaging usage, and patients’ attitudes about receiving text messages when implementing an SMS intervention in Chinese hospitals.…”
Section: Introductionmentioning
confidence: 99%